A performance history of The fair penitent - McGirr, Elaine M. 1972- (Cambridge University Press, 2024)
Theatre is the most ephemeral of art forms. It is a truism that the ephemeral performance text is divorced from the static published play text. This Element is of the eighteenth-century performance history of The Fair Penitent demonstrates the interrelation of print and performance and models how readers can recover elements of performance through close attention to text. Traces of performance adhere to the mediascape in playbills and puffs, reviews and accounts. The printed text also preserves traces of performance in notation and illustration. By analysing traces found in performance trends, casting decisions, publication histories and repertory intertexts, this Element recovers how The Fair Penitent was interpreted at different points in the century and explains how a play that bombed in its first season could become a repertory staple
Title from publisher's bibliographic system (viewed on 28 Feb 2024)
Keywords: Rowe, Nicholas / 1674-1718 / Criticism and interpretation; Rowe, Nicholas / 1674-1718 / Fair penitent; Rowe, Nicholas / 1674-1718 / Dramatic production; Rowe, Nicholas -- 1674-1718 -- The fair penitent; Geschichte 1703-1800; Aufführung